(7, 8-Dicarba-nido-undecaboran-7-yl)acetic acid: synthesis of individual enantiomers and the first example of the determination of the absolute configuration of chiral monosubstituted nido-carborane. (30th August 2022) - Gruzdev, Dmitry A.; Telegina, Angelina A.; Chulakov, Evgeny N.; Levit, Galina L.; Krasnov, Victor P.
Abstract : Starting from achiral closo -carborane and using natural amino acid as chiral auxiliary, individual ( R P )- and ( S P )-enantiomers of C-monosubstituted nido -carboranes were obtained. Abstract : Individual ( R P )- and ( S P )-enantiomers of planar-chiral (7, 8-dicarba- nido -undecaboran-7-yl)acetic acid were obtained for the first time by deboronation of the derivatives of achiral (1, 2-dicarba- closo -dodecaboran-1-yl)acetic acid containing residues of natural amino acids and ethylenediamine, followed by separation and hydrolysis of diastereomeric derivatives. An alternative route for the preparation of enantiopure ( nido -carboran-7-yl)acetic acid starting from an enantiopure amino ester based on closo -carborane of known configuration made it possible for the first time to assign the absolute configuration of structurally simple C-monosubstituted nido -carborane derivatives. Using the example of introducing an amino group into position 10 of the carborane fragment of (7, 8-dicarba- nido -undecaboran-7-yl)acetic acid, we have demonstrated the possibility of obtaining planar-chiral functional derivatives of nido -carborane.